Examining Translation Practices in Teaching French as A Foreign Language in the South African Educational Context - Jean Claude Loh Yai (Canadian Journal of Language and Literature Studies, 2025)
The use of translation in foreign language teaching has hardly been encouraged by most teachers who prefer the direct method. Most educational syllabus highlights the listening, speaking, reading and writing skills and translation has hardly been seen as a pedagogical tool or technique that can enhance these skills. This study therefore, sought to investigate the translation practices used in teaching French as a foreign language in South Africa. The study primarily aims to examine how translation practices influence students’ engagement and proficiency in a multilingual context. To conduct this study, the qualitative research approach was employed. Questionnaires and interviews were used to collect data which were analysed using the thematic analysis. Key ethical considerations were followed to enhance privacy and confidentiality of participants drawn from schools within the Gauteng province. The findings of the study established that translation practices had major impact on students’ performance in a French language task. The study also established that, culturally relevant didactic material enhances students’ engagement and motivation. This study concludes with some recommendations and limitations aimed at enhancing the use and implementation of translation strategies in the French classroom set-up.